1999
DOI: 10.1080/014492999118995
|View full text |Cite
|
Sign up to set email alerts
|

Text entry using soft keyboards

Abstract: Abstract. Text entry rates are explored for several variations of soft keyboards. We present a model to predict novice and expert entry rates and present an empirical test with 24 subjects. Six keyboards were examined: the Qwerty, ABC, Dvorak, Fitaly, JustType, and telephone. At 8± 10 wpm, novice predictions are low for all layouts because the dominant factor is the visual scan time, rather than the movement time. Expert predictions are in the range of 22± 56 wpm, although these were not tested empirically. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(118 citation statements)
references
References 19 publications
4
105
1
3
Order By: Relevance
“…Learning curve is customary in studies of human performance and learning to fit a regression curve in the form of the power law of learning [2]. As Fig.…”
Section: Experiments and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning curve is customary in studies of human performance and learning to fit a regression curve in the form of the power law of learning [2]. As Fig.…”
Section: Experiments and Evaluationmentioning
confidence: 99%
“…The methods are intuitive without any learning process. Selection-based methods, however, are slow, requiring many movements to select one letter [2]. Users quickly become bored.…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, in light of Fitts law, Silfverberg, et al proposed a new mathematical model for predicting the text for the users while typing [18]. This predictive model helps users to enter the text very quickly, which was intended to diminish the number of keystrokes.…”
Section: Related Workmentioning
confidence: 99%
“…Touchscreen keyboards are a fundamental application for touchscreen interfaces and are used in several application areas. The key arrangement for touchscreen keyboards typically uses the standard Qwerty arrangement because users can transfer their skills and experience gained using common hardware keyboards [5]. Previous studies have shown that the text entry rate for a touchscreen keyboard is considerably slower than that for hardware Qwerty keyboard, even for expert typists [6,7].…”
Section: Introductionmentioning
confidence: 99%